The 1993-1994 VSC Lady Blazers - Valdosta State University, Athletics Department (Valdosta State University, 1994)
This year's two seniors are pictured with head coach Charles Cooper and assistant Angie Dilliner on the bridge leading to the main entrance to The Complex, home of Lady Blazer basketball. The seniors are Yolanda Chester, left, and Ivey Vickers.
### Players: Laurie Owens; Yolanda Chester; Ivey Vickers; Stephanie Smith; Melissa Griffin; Kathy Kennedy; Deidre Williams; Amy Lueken; Yolanda Jenkins; Dawn Wynn; Staci Miller; Natasha Horn; Amy Seidiing; ### Staff: Herb Reinhard; Charles Cooper; Angie Dilliner; Bill England; Jim Madaleno; Lori Howard; Steve Roberts; Rodney Warren; John Roberts; Bill Roberts; Larry Lampert;
Keywords: Athletics; Basketball; Lady Blazers